Aquarelles et dessins japonais des 18e et 19e siècles. - Musée d'Ixelles (Ixelles : Musée d'Ixelles, 1981)
Bagai, Totoki ; Bairei, Kono ; Baitei, Ki ; Bokusen, Yamaoka ; Buncho, Tani ; Chikuto, Nakabayashi ; Chinnen, Onishi ; Chinzan, Tsubaki ; Chiryu ; etc.
Aquarelles et dessins japonais des 18e et 19e siècles, Musée d'Ixelles, 19.11.1981 - 31.01.1982
boek